3D Macro‐Mesoporous TiO2‐Graphene Oxide (GO) Composite with Enhanced Catalytic Performance in the Epoxidation of Styrene and its Derivatives. Issue 7 (19th May 2016) - Bian, Gang; Jiang, Pingping; Zhao, Hui; Jiang, Kelei; Hu, Ling; Dong, Yuming; Zhang, Weijie
Abstract: It has been widely accepted that graphene oxide shows promising potential on facilitating electron transfer which can enhance catalytic properties. In this work, a 3D ordered macro‐mesoporous titania composites with graphene oxide (TiO2 ‐GO) were synthesized through a confinement self‐assembly method and applied to the epoxidation reactions of styrene and its derivatives. XRD, BET, SEM, TEM and XPS were used to characterize the hierarchically ordered composites. The incorporation of GO in the TiO2 ‐GO composite made the catalyst structure rather stable and dramatically improved the catalytic activity compared with pure mesoporous TiO2, the conversion of styrene in epoxidation raised from 53.68 % to 93.34 % as the TiO2 combined with GO. Based on the experimental results, the mechanism was proposed to study the π‐π interaction between GO and styrene, which was further confirmed by Photoluminescence (PL) analysis, polarization and cyclic voltammetry curves. In short, combining GO with metallic oxide materials will enhance the catalytic performance in epoxidation reactions and such designed strategy can extend to other catalytic reactions. Abstract : An ordered macro‐mesoporous titania composites with graphene oxide (TiO2 ‐GO) was synthetized through a confinement self‐assembly method. Compared with the pure mesoporous titania (TiO2 ), TiO2 ‐GO had a superior catalytic activity for styrene and its derivatives.